Pemosisian Siswa dalam Praktik Diskusi Kelompok pada Pembelajaran Matematika - Alhikma, Nur Alaviyah; Subanji, Subanji; Muksar, Makbul (Universitas Nahdlatul Ulama Blitar, 2025)
This study aims to describe student positioning in mathematics group discussion practices. This research method is descriptive qualitative. The research subjects were 8 junior high school students who were divided into 2 groups. The researcher conducted the research for 3 meetings. Each meeting students were given questions about tubes and cones. Data collection was carried out by means of observation, documentation, and interviews regarding student interactions, conversations, and discussion activities. Data analysis was carried out by coding student conversations through negotiation and positioning systems. The results of the study stated that positioning is dynamic and changing, each student has a tendency in one of the positioning, and motivation is one of the characteristics of students who are positioned as facilitators. Knowing the positioning of each student is used as a reference for teachers to understand student characteristics, the right learning style for students, how to communicate with students, and give objective grades to students.